The patient safety in extracorporeal blood purification treatments of critical patients - Nalesso, Federico; Garzotto, Francesco; Martello, Tiziano; Contessa, Cristina; Cattarin, Leda; Protti, Mariapaola; Di Vico, Valentina; Stefanelli, Lucia Federica; Scaparrotta, Giuseppe; Calò, Lorenzo A. (Frontiers in Nephrology, 2022)
Today Health Systems are complex both due to technological development in diagnostic and therapeutic procedures and to the complexity of the patients that are increasingly older with several comorbidities. In any care setting, latent, organizational and systematic errors can occur causing critical incident harmful for patients. Management of patients with acute kidney injury (AKI) requires a multidisciplinary approach for the diagnostic-therapeutic-rehabilitative path that can also require an extracorporeal blood purification treatment (EBPT). The complexity of these patients and EBPT require a clinical risk analysis and the introduction of protocols, procedures, operating instructions, and checklists in order to reduce clinical risk through promotion of the safety culture for all care providers. Caregivers must acquire a series of tools to evaluate the clinical risk in their reality to prevent incidents and customize patient safety in a proactive and reactive way. Established procedures made more needed by the Covid 19 pandemic, can help to better manage patients in critical care area with intrinsic higher clinical risk. This review analyzes the communication and organizational aspects that need to be taken into consideration in the management of EBPT in a critical care setting by providing tools that can be used in order to reduce the clinical risk. This review is mostly addressed to all the caregivers involved in the EBPT in Critical Care Nephrology and in the Intensive Care Units.